Genetic variation among Iranian alfalfa (Medicago sativa L.) populations based on RAPD markers - Mohammadzadeh, Fatemeh; Monirifar, Hassan; Saba, Jalal; Valizadeh, Mostafa; Haghighi, Ahmad Razban; Zanjani, Bahram Maleki; Barghi, Maryam; Tarhriz, Vahideh (Bangladesh Journal of Plant Taxonomy, 2011)
Genetic diversity among and within 10 populations of Iranian alfalfa, from different areas of Azarbaijan, Iran was analyzed by screening DNA from seeds of individual plants and bulk samples. In individual study, 10 randomly amplified polymorphic DNA (RAPD) primers produced 156 polymorphic bands and a high level of genetic diversity was observed within populations. The averages of total and within population genetic diversity were 0.2349 and 0.1892, respectively. Results of analysis of molecular variance (AMOVA) showed the great genetic variation existed within populations (81.37%). These Results were in agreement with allogamous and polyploid nature of alfalfa. Cluster analysis was performed based on Nei’s genetic distances resulting in grouping into 3 clusters which could separate breeding population from other populations. Results of cluster analysis were in consistent with morphological and geographical patterns of populations. The results of bulk method were different from individual analysis. Our results showed that RAPD analysis is a suitable method to study genetic diversity and relationships among alfalfa populations. Keywords: Alfalfa; RAPD; Genetic diversity; Analysis of Molecular Variance; Cluster analysis. DOI: http://dx.doi.org/10.3329/bjpt.v18i2.9296 Bangladesh J. Plant Taxon. 18: (2): 93-104, 2011 (December)